Leadership in sport - study with futsal coaches in “under 17” and senior levels - Honório, Samuel (2018)
Submitted by Samuel Honório (samuelhonorio@ipcb.pt) on 2018-09-18T13:32:00Z No. of bitstreams: 1 LEADERSHIP IN SPORT - STUDY WITH FUTSAL COACHES IN “UNDER 17” AND SENIOR LEVELS_JHSE_eng_FV.pdf: 251914 bytes, checksum: cd1b163fefab65885ea6d856a0c94d99 (MD5)